Finnish Forest Sector Economic Outlook 2021–2022 : Executive Summary - Viitanen, Jari; Mutanen, Antti; Kniivilä, Matleena; Haltia, Emmi; Viitala, Esa-Jussi; Kallioniemi, Marja; Härkönen, Kari; Leppänen, Jussi; Uotila, Esa; Routa, Johanna (Natural Resources Institute Finland (Luke), 2021)
The gradual fading of the effects of the COVID-19 pandemic and the continuation of economic recovery will be reflected in the global economy and increase the production and export volumes of Finnish forest industry products in 2021. In Finland, the growing demand for roundwood increases the removals of industrial roundwood, raises stumpage prices, and improves employment and profitability in the forest sector. In 2022, along with the slowing growth of the world economy, the growth rate of production and export volumes of many forest products will decrease, and paper production and exports will start to decline again. The export prices for sawnwood and pulp, stumpage prices, and roundwood import volumes are also declining. The removals of industrial roundwood will remain close to the current year's level in more than 65 million cubic meters. The executive summary is a translation of the summary of the Finnish original publication ”Metsäsektorin suhdannekatsaus 2021-2022”, and is based on information available in October 2021.
Keywords: forest sector; forest products industry